Pengaruh Kecepatan Pengadukan dan Waktu Kontak Terhadap Penyerapan Fenol Menggunakan Adsorben C-SinamalKaliks[4]Resorsinarena Hasil Sintesis Limbah Minyak Kayu Manis (Cinnamomum burmanii) - Dewi Kristina; Sri Benti Etika; Edi Nasra; Budhi Oktavia (Jurnal Periodic Jurusan Kimia UNP, 2022)
Several industries produce liquid waste that pollutes the environment. The industrial waste produced usually contains phenol. Phenol is included in hazardous waste so that its presence in the environment needs to be considered. To overcome this environmental problem, the adsorption method can be applied using synthesized compounds such as C-CinnamalCalix[4]Resorcinarene (CCCR). CCCR is a derivative of Calix[4]Resorcinarene which can act as a host for cations, anions, and neutral molecules because it has a unique shape that has an active group, which can form hydrogen bonding with phenol solution. the purpose of this study was to determine the optimum conditions with variation in stirring speeds of 50, 100, 150, 200, and 250 rpm and contact times of 45, 60, 75, 105, and 150 minutes. phenol was analyzed using a UV-Vis spectrophotometer (Specord 210). adsorption phenol with CCCR obtained optimum conditions at stirring speeds of 200 rpm with an adsorption capacity of 2.016 mg/g and contact times of 60 minutes with an adsorption capacity of 2.079 mg/g.